Auditor evaluation of others' credibility: A review of experimental studies on determinants and consequences. Issue 1 (October 2015) - Maksymov, Eldar
Abstract: I synthesize the extant experimental literature examining auditor evaluation of others' credibility published in six top accounting journals over the last three-and-a-half decades. I adapt the original definition of credibility byHovland, Janis, and Kelley (1953) : the extent of perceiving someone as competent and trustworthy. Audit guidance requires auditors to consider credibility of management, internal auditors, and staff, yet the research literature on auditor evaluation of others' credibility is fragmented and scarce, limiting our understanding of determinants and consequences of auditor evaluations. I develop a framework for analysis of research on auditor evaluation of others' credibility and review extant literature by types of examined effects (determinants of credibility vs. consequences of credibility) and by examined credibility components (competence, trustworthiness, or both). Throughout the literature review I suggest areas for future research.